PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN SKPD (Studi Pada Pemerintah Daerah Kabupaten Kampar) - Dhedy Triwardana; Yusralaini '; Susilatri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to analyze the influence of implementing accounting government standard, implementing of accounting financial system and competency of human resources to the quality of financial statement SKPD. Object of this research is department of SKPD Kampar. There are seventy eight questionnaires were sent, but only sixty nine questionnaires are returned. That data are analyzed by linear regression method and SPSS program version 19. The results of this research showed implementing accounting government standard has an effect to the quality of financial statement SKPD with 0,003 significance, implementing of accounting financial system has an effect to the quality of financial statement SKPD with 0,000 significance and competency of human resources has an effect to the quality of financial statement SKPD with 0,000 significance. The results of this research also showed that coefficient R square is 94,1%. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well. While the remaining influenced by other variables not included in the regression models were not included in this study. All variables also have strong relation with variable dependents in this research.Keywords: Government, Financial System, Human Resources And Financial Statement